Assessment of the possibilities of using alternative fuels in the cement industry - Niekurzak, Mariusz; Mysłowski , Jaromir; Lewicki, Wojciech (Economics and Environment, 2025)
The article aims to assess the possibility of using alternative fuels in the cement industry. The research focuses on evaluating the use of alternative fuels, considering their calorific value, the share of biomass content, the impact on the CO2 emission factor, and the possibility of achieving possible economic benefits. The methodology includes the analysis of production data and the calculation of savings resulting from the use of alternative fuels. On this basis, ecological aspects were also indicated that should be taken into account when analysing the profitability of the investment. The conclusions show that by using alternative fuels, CO2 emissions and production costs are reduced, while there is no negative impact on efficiency and production volume. For practice, it was important to confirm that alternative fuels can also find practical application in the cement industry, and investing in renewable energy sources by cement production plants fits into the goals and directions of development related to sustainable management of resources according to the win-win principle.